Surgical ablation of ventricular tachycardia in patients with repaired tetralogy of Fallot†. (22nd December 2018) - Caldaroni, Federica; Lo Rito, Mauro; Chessa, Massimo; Varrica, Alessandro; Micheletti, Angelo; Pappone, Carlo; Giamberti, Alessandro
Abstract: OBJECTIVES: Life expectancy of patients with repaired tetralogy of Fallot is normal until adulthood, when it becomes burdened by major complications such as cardiac arrhythmias and heart failure. Ventricular tachycardia (VT), associated with electrical conduction abnormalities in anatomical isthmuses, is the most common complication and is refractory to medical therapy. The arrhythmogenic sources can be surgically ablated during reoperations for pulmonary valve incompetence. The purpose of our study is to evaluate the safety and effectiveness of surgical radiofrequency ablation during PVR and its long-term impact on the occurrence of cardiac events. METHODS: A total of 118 patients with repaired tetralogy of Fallot underwent reoperation for pulmonary valve regurgitation in IRCCS-Policlinico San Donato between January 2002 and February 2016. Twenty patients with risk factors for ventricular arrhythmia underwent EP testing and were found positive. The mean QRS duration was 178 ms. Right ventricular dysfunction was present in all the patients, and 20% had associated tricuspid regurgitation. The cohort ( N = 20), with positive EP study, underwent pulmonary valve replacement and concomitant intraoperative ventricular surgical radiofrequency ablation, targeting the slow conducting isthmuses identified during preoperative electroanatomical mapping. All patients were reviewed at 1 month, 3 months and 6 months with clinical evaluation, echocardiography, ECG and implantable cardioverter-defibrillator interrogation. At 6 months, a postoperative electrophysiological study was performed in all patients, and a cardioverter defibrillator was implanted as primary preventive measure in patients with residual inducible VT. RESULTS: Pulmonary valve replacement and surgical ventricular radiofrequency ablation were performed in all cases. One patient died while on V-V extracorporeal membrane oxygenation (ECMO) due to respiratory failure. There was no late mortality. Follow-up was complete with a median of 6.5 years. During the postoperative EPS study, inducible VT was found in 15.7% of patients who received an implantable cardioverter-defibrillator, whereas VT could no longer be induced in the remaining patients. No procedure-related complication was observed, and freedom from ventricular arrhythmia was 94% and 89.5% at 1 year and 5 years, respectively. CONCLUSIONS: Pulmonary regurgitation and right ventricular dysfunction correlate with VT and SCD, but valve replacement alone does not reduce the risk of ventricular tachyarrhythmias. Intraoperative ventricular ablation during reoperation for pulmonary regurgitation prevents the occurrence of ventricular arrhythmias in the early and medium term. Accordingly, this technique may be proposed as a safe associated procedure in selected patients.